By Design: Aligning Structure with Values to Impact Outcomes in a Public Utility Model - Bartholomew, Kathleen (Journal of Public Health International, 2021)
The lived experiences of thousands of health care providers demonstrates an inconguence in values while giving us a tremendous amount of information - if we listen. At every level behaviors are compromised in a structure when the values of the providers are not aligned with the system. Over time, statistics as well as disease become so normalized that the status quo dominates perceptions and inhibits action. The United States will continue to have mediocre to poor outcomes unless the ethical foundation of the system is fundamentally altered to profit on wellness. “You never change things by fighting the existing reality. To change something, build a new model that makes the existing model obsolete.” Buckminster Fuller 1